Influence Analysis Of Pt Bsm Msmes (Micro, Small And Medium Enterprises) Customer Motivation On Loan Decisions Through Perceived Quality As A Moderating Variable - Sarwoto Sarwoto; Saparuddin Siregar; Isnaini Harahap (Proceeding International Seminar of Islamic Studies, 2019)
This study aims to determine the effect of motivation of MSMEs in making loan decisions which will include the impression of quality as a moderating variable. The study was conducted on SMEs who became loan customers of PT BSM as many as 150 people. The criteria of the respondents were having loan between IDR 50 million to IDR 100 million with smoothly payment status. The data analysis method uses SPSS version 22.